PERAN HUKUM TERHADAP MASUKNYA DANA TRANSFER YANG BUKAN HAK MILIK - Buamona, Mita Wahyuni; Apriani, Rani (Peneliti.net, 2024)
According to the Law of the Republic of Indonesia Number 7 of 1992, a bank is a business entity that collects funds from the public in the form of savings and distributes them to the public in the form of credit and/or other forms in order to improve the people's standard of living. Thus, what if one of the information that emerged recently was the occurrence of mysterious funds transfers or it could be said that they did not know where the funds came from in a customer's account, and the amount entered was quite large and exceeded the reasonable limit. The purpose of this paper is to find out what if seen from a legal perspective, the results of the study show that there are rules regarding how the actions that need to be taken by customers, the initial action is that the customer can report directly to the bank concerned. keywod : fund, legal basis, customer